Status Pekerjaan Ibu Dengan Perkembangan Balita Usia 3 Sampai 5 Tahun Di PAUD Permata Hati Al Mahalli - Nurul Oktavia Setia Utami; Era Revika; Nur’aeni Eka Sari (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2023)
Background: Children can optimally achieve 4 aspects of development (fine motor,gross motor, language, and social) if they get stimulation from an early age. Manyfactors affect the growth and development of children. Parents or companions can dothe stimulation. Parents, especially mothers, play an essential role in the process ofgrowth and development of children. Currently, mothers have various roles, one ofwhich is being a working mother.Objective: This study aimed to determine the correlation between the mother'semployment status and the development of toddlers aged 3 to 5 years at Permata HatiAl Mahalli Method: This is an observational analytic study with a cross-sectional approach. Thisstudy used total sampling to get 35 respondents of mothers and toddlers. Datacollection was carried out using mother respondent identity sheets and the results ofthe Pre-screening Developmental Questionnaire (PDQ) for assessing toddlerdevelopment. Data analysis in this study was carried out using Chi-Square.Result: This study showed that there were 7 (35%) toddlers with dubious developmentout of 20 working mothers and 1 (6.7%) toddler with dubious development out of 15non-working mothers. The chi-square test results showed df = 1 at a significant levelof 5% with a p-value of 0.048 <0.05.Conclusion: Mother's employment status is significantly correlated with thedevelopment of toddlers aged 3 to 5 years at Permata Hati Al MahalliKeywords: Mother's employment status, toddlers’ development